Pipistrellus nathusii Keyserling & Blasius 1839 ... - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2019)
22. Nathusius’s Pipistrelle Pipistrellus nathusii French: Pipistrelle de Nathusius / German: Rauhautfledermaus / Spanish: Pipistrela de Nathusius Taxonomy. Vesperugo nathusii Keyserling & Blasius, 1839, Berlin, Germany. Pipastrellus nathusii appears to be close to the P. kuhlii complex, which includes paraphyletic P. kuhliiand P. maderensis. Monotypic. Distribution. Most of Europe (from Ireland and Iberian Peninsula E to Russia and W Kazakhstan), Turkey, and Caucasus; also on Mediterranean Is such as Crete or Mallorca. Descriptive notes. Head-body 44-54 mm, tail 30-40 mm, ear 10-5-16 mm, forearm 32-2-37-1 mm; weight 6-15-5 g. Fur color of Nathusius’s Pipistrelle changes seasonally, being dark brown or gray brown in winter and reddish in summer. Fur is long and uniformly colored, but venteris slightly paler or more yellowish than dorsum. Proximal one-half of uropatagium is covered by fur. Bare skin is dark brown, snout is short and rounded, and ears are triangular and short, with slender and rounded ... : Published as part of Don E. Wilson & Russell A. Mittermeier, 2019, Vespertilionidae, pp. 716-981 in Handbook of the Mammals of the World – Volume 9 Bats, Barcelona :Lynx Edicions on page 773, DOI: 10.5281/zenodo.6397752 ...